An Introduction to Forest Governance, People and REDD+ in Latin America: Obstacles and Opportunities - Larson, A.M.; Petkova, E. (MDPI, 2011)
REDD+ is a potentially significant financial mechanism for shifting the incentives from deforestation and land use change to forest conservation and sustainability. Even though REDD+ is not primarily a governance reform, it will affect or be affected by forest governance, it can improve forest governance or be undermined by its failures and, therefore, it depends on good forest governance if it is to be efficient, effective and equitable. This article provides an overview of key issues in forest governance in Latin America and discusses the risk and opportunities for REDD+. Though progress has been made in some areas, there is still much to be done, and REDD+ could reinforce or be undermined by problematic governance tendencies that affect its effectiveness, ability to decrease carbon emissions, and/or its legitimacy. The article recommends priority investments in institutional capacity, inter-institutional negotiation mechanisms, citizen participation and safeguards for forest-based populations.